DEVELOPMENT OF FLEXIBLE ELECTRODE FOR LITHIUM-ION BATTERIES - Adylkhanova, Assyl (Nazarbayev University School of Engineering and Digital Sciences, 2022)
Flexible batteries have gained much scientific interest due to the rapid development of advanced technology. Among the materials studied to improve the performance of flexible lithium-ion batteries (LIBs), lithium-sulfur batteries have attracted more attention due to their high theoretical energy density. Especially recently, organic conductive polymers are being actively studied due to their unique properties. For instance, Poly(3,4- ethylenedioxythiophene):poly(styrene sulfonate) or PEDOT:PSS can be distinguished among other conductive polymers. PEDOT:PSS received significant attention due to its excellent chemical stability, flexibility and high conductivity. This work aims to synthesize a freestanding flexible polymer electrode via the doctor-blade method. The prepared composite (sulfur @ MWCNT @ PEDOT:PSS film) was characterized by scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS). Cycling voltammetry (CV), electrochemical impedance spectroscopy (EIS), and galvanostatic charge-discharge analyses were applied to study the electrochemical properties. The as-prepared electrode exhibited a high specific capacity of about 550 mAh/g at 1 C after 100 cycles, achieving Coulombic efficiency of 100% after the second cycle.
Keywords: type of access: gated access; PEDOT:PSS; flexible lithium-ion batteries; LIBs; lithium-sulfur batteries; flexible electrode; Research Subject Categories::TECHNOLOGY